Advanced reconstructive techniques for surgical management of extensive skin defects due to post-burn scarring: a systematic review - Huilca Villalba , Génesis Karolina; Castro Ibáñez , Fernanda Ximena; Diaz Carbajal , Any Yareli; Portilla Muñoz, Sebastián David; Cuello Carranza, Adlay Jambick; Ruiz Rodriguez , Jaret Damar; Alvarez Arroyo, José Javier (Arandu UTIC, 2024)
Recent advancements in reconstructive techniques for burn-induced skin defects have improved functional and aesthetic outcomes to enhance life quality of burn survivors. A wide range of innovative methods such as flap surgeries advancements or laser therapies and tissue expansion techniques are now available in the markets and their use has been widely explored for management of extensive post-burn scarring. According to studies the use of latest technological innovations and microvascular free tissue transfer, Z-plasty and trapeze flaps have excellent success rates for contracture release, scar reduction, and functional restoration. Laser treatments that have shown promise in decreasing scar thickness and increasing suppleness include stromal vascular fraction therapy and CO2 fractional lasers. There remain persisting issues like limited long-term data, expense, and technical complexity. In order to evaluate the clinical effectiveness, drawbacks, and potential future directions of these reconstructive techniques in burn care, this review summarizes recent research.